2023
DOI: 10.15252/embr.202255532
|View full text |Cite
|
Sign up to set email alerts
|

T cell‐dependent bispecific antibodies alter organ‐specific endothelial cell–T cell interaction

Abstract: Preclinical and clinical studies demonstrate that T cell-dependent bispecific antibodies (TDBs) induce systemic changes in addition to tumor killing, leading to adverse events. Here, we report an indepth characterization of acute responses to TDBs in tumorbearing mice. Contrary to modest changes in tumors, rapid and substantial lymphocyte accumulation and endothelial cell (EC) activation occur around large blood vessels in normal organs including the liver. We hypothesize that organ-specific ECs may account fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 84 publications
1
0
0
Order By: Relevance
“…At the same time, they also upregulated cytokine genes, including IL6 and IL1B , and chemokine genes, including CXCL9, CXCL10, CXCL11, CCL2, CCL5 , and CCL8 , suggestive of their role in further amplifying the cytokine release cascade and recruiting surrounding immune cells. In line with our findings, Himmels and colleagues recently reported that cytokine and chemokines induced by T-cell–dependent bispecific antibodies can mediate the activation of endothelial cells, which results in adhesion and infiltration of peripheral T cells in tumor and/or healthy tissues ( 41 ). Altogether, these data highlight the importance of vasculature in the safety and efficacy of T-cell–engaging therapies.…”
Section: Discussionsupporting
confidence: 92%
“…At the same time, they also upregulated cytokine genes, including IL6 and IL1B , and chemokine genes, including CXCL9, CXCL10, CXCL11, CCL2, CCL5 , and CCL8 , suggestive of their role in further amplifying the cytokine release cascade and recruiting surrounding immune cells. In line with our findings, Himmels and colleagues recently reported that cytokine and chemokines induced by T-cell–dependent bispecific antibodies can mediate the activation of endothelial cells, which results in adhesion and infiltration of peripheral T cells in tumor and/or healthy tissues ( 41 ). Altogether, these data highlight the importance of vasculature in the safety and efficacy of T-cell–engaging therapies.…”
Section: Discussionsupporting
confidence: 92%